High Expression of H3K27me3 in Human Hepatocellular Carcinomas Correlates Closely with Vascular Invasion and Predicts Worse Prognosis in Patients - Mu-Yan Cai; Jing-Hui Hou; Hui-Lan Rao; Rong-Zhen Luo; Mei Li; Xiao-Qing Pei; Marie C.M. Lin; Xin‐Yuan Guan; Hsiang‐Fu Kung; Yi-Xin Zeng; Dan Xie (2010)
It has been suggested that trimethylation of lysine 27 on histone H3 (H3K27me3) is a crucial epigenetic process in tumorigenesis. However, the expression dynamics of H3K27me3 and its clinicopathological/prognostic significance in hepatocellular carcinoma (HCC) are unclear. In this study, immunohistochemical analysis (IHC) was used to examine protein expression of H3K27me3 in HCC tissues from two independent cohorts and corresponding nontumorous hepatocellular tissues by tissue microarray. The optimal cutpoint of H3K27me3 expression was assessed by the X-tile program. Our results showed that the cutpoint for high expression of H3K27me3 in HCCs was determined when more than 70% of the tumor cells showed positive staining. High expression of H3K27me3 was observed in 134 of 212 (63.2%) and 76 of 126 (60.4%) of HCCs in the testing and validation cohorts, respectively. Correlation analysis demonstrated that high expression of H3K27me3 in HCCs was significantly correlated with large tumor size, multiplicity, poor differentiation, advanced clinical stage and vascular invasion (P < 0.05). In addition, high expression of H3K27me3 in HCC patients was associated closely with shortened survival time, independent of serum α-fetoprotein levels, tumor size and multiplicity, clinical stage, vascular invasion and relapse as evidenced by univariate and multivariate analysis in both cohorts (P < 0.05). In different subsets of HCC patients, H3K27me3 expression was also a prognostic indicator in patients with stage II tumors (P < 0.05). Thus, these findings provide evidence that a high expression of H3K27me3, as detected by IHC, correlates closely with vascular invasion of HCCs and is an independent molecular marker for poor prognosis in patients with HCC.